An economic study of small scale cattle fattening enterprise of Rajbari district (Journal of the Bangladesh Agricultural University, 2011)
The small scale cattle fattening enterprise is represents an important component of the agribusiness sector of the economy with great economic, income, poverty reduction and social implications. A large number of farmers involved in cattle fattening just before 3 or 4 months of Eid-ul-Azha (Muslim festival), when they sell the animals with profitable prices. Cattle fattening for beef production have become an important business of the small farmers in Bangladesh. This study examined the profitability as well as operational economics efficiency of cattle fattening enterprise of Rajbari District. Data used to achieve this objective was obtained from 120 nomadic farmers, which were randomly selected using a multi-stage sampling procedure. Data were generated using a survey schedule as well as direct observation (cost-route method). Descriptive statistics, economics analysis as well as operational efficiency index were used to analyze the data. Results showed that small scale cattle fattening enterprise were profitable and flexible. A net enterprise income of BDT 5559 per cattle was realized by an average enterprise in study area. It was also shown that operational efficiency was not generally high among the entrepreneur. Based on these results, the study advised less efficient entrepreneurs to adopt the practices of the efficient ones in order to make the enterprise more profitable. The study shows that small scale cattle fattening enterprise is profitable due to agribusiness context. Farmers used three years old cattle for beef fattening. Cattle fattening period is 4.5 months in rural study areas of Rajbari district in Bangladesh. Keywords: Economic efficiency; Cattle farming; Profitability DOI: http://dx.doi.org/10.3329/jbau.v9i1.8756 JBAU 2011; 9(1): 141-146